2015
DOI: 10.1002/2015ja021276
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of MLT tides revealed by a meteor radar chain based on Hough mode decomposition

Abstract: Seasonal variations of different tides in the mesosphere and lower thermosphere are investigated from wind observations of a meteor radar chain on the basis of Hough mode decomposition. First, the observed winds are decomposed into different (diurnal, semidiurnal, and terdiurnal) tidal components. Different seasonal patterns are revealed for each component. Pronounced semiannual oscillation (SAO) is presented in the diurnal component, while latitude‐dependent seasonal variation is found in the semidiurnal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…In addition, a semiannual variation with maxima eastward wind in summer and a secondary maximum during winter were observed between 85 and 96 km over Mohe. These results are comparable with that of previous study along 120°E longitude in NH (Yu et al, 2015). The differences in structure between the four stations are mainly due to different latitudes, which are consistent with previous global model studies and the observational result referenced therein Fleming et al, 1990;Fomichev et al, 2002;Hedin et al, 1996;Portnyagin et al, 2004;Portnyagin & Solovjova, 2000).…”
Section: Climatology Of the Horizontal Wind And Gw Momentum Fluxessupporting
confidence: 93%
“…In addition, a semiannual variation with maxima eastward wind in summer and a secondary maximum during winter were observed between 85 and 96 km over Mohe. These results are comparable with that of previous study along 120°E longitude in NH (Yu et al, 2015). The differences in structure between the four stations are mainly due to different latitudes, which are consistent with previous global model studies and the observational result referenced therein Fleming et al, 1990;Fomichev et al, 2002;Hedin et al, 1996;Portnyagin et al, 2004;Portnyagin & Solovjova, 2000).…”
Section: Climatology Of the Horizontal Wind And Gw Momentum Fluxessupporting
confidence: 93%
“…The semidiurnal tide is the main dominant tidal component in both systems, which fits with the results of Hoffmann et al (2010). Yu et al (2015) showed, however, increasing tidal amplitudes with increasing heights for several locations. The amplitudes in tidal modes vary with height, season, component, and location.…”
Section: Discussionsupporting
confidence: 78%
“…With the support of Chinese Meridian Project, four meteor radars were installed at Mohe (53.5°N, 122.3°E), Beijing (40.3°N, 116.2°E), Wuhan (30.5°N, 114.6°E), and Sanya (18.3°N, 109.6°E) in 2011 around the geographic longitude of 120°E. Further details regarding these meteor radars can be found in previous literatures (Liu et al, 2017; Ma et al, 2017; Xiong et al, 2013; Yu et al, 2013, 2015). Besides these four radars, the Kunming meteor radar (25.6°N, 103.8°E), which belongs to the China Research Institute of Radio Wave Propagation, has been operated since year 2011.…”
Section: Meteor Radar Data and Methods Of Analysismentioning
confidence: 90%